2020
DOI: 10.12669/pjms.36.3.1490
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin-D deficiency is related to severity of liver damage in Hepatitis-C patients

Abstract: Objective: Serum Vitamin-D plays pivotal role in inflammatory and infectious diseases; among them liver infections are more distinct. This study was aimed to determine Vitamin-D status in HCV-infected patients and healthy controls in Faisalabad, Pakistan. Methods: We performed randomized cross-sectional study of 74 individuals from 20th August, 2017 to 20th February 2018 at The University of Faisalabad and Dar us Shifa Clinic, Faisalabad. Fifty-one patients were hepatitis C RNA-PCR positive (22 compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
0
0
1
Order By: Relevance
“…Inverse relationship between severity of liver disease and vitamin D levels was reported as 55.2% of decompensated cirrhosis patients were Vitamin-D deficient compared to 13.6% in compensated cirrhosis by Falak etal (22) In this study we found that in patients with liver cirrhosis vitamin D has inverse relationship with Child Pugh class as deficiency is more common as the Child class progresses. Patients with Child A cirrhosis 6/10 (60%) had deficiency, with child B 66/82 (80.5%) while with Child C 72/78 (92.3%) had deficiency of Vitamin D3.…”
supporting
confidence: 50%
“…Inverse relationship between severity of liver disease and vitamin D levels was reported as 55.2% of decompensated cirrhosis patients were Vitamin-D deficient compared to 13.6% in compensated cirrhosis by Falak etal (22) In this study we found that in patients with liver cirrhosis vitamin D has inverse relationship with Child Pugh class as deficiency is more common as the Child class progresses. Patients with Child A cirrhosis 6/10 (60%) had deficiency, with child B 66/82 (80.5%) while with Child C 72/78 (92.3%) had deficiency of Vitamin D3.…”
supporting
confidence: 50%
“…Another study has also shown significantly low vitamin D levels in hepatitis C virus patients as compared to healthy subjects (Gao et al, 2016). Furthermore, this study showed the prevalence of 54.8% of vitamin D deficiency (referring to serum 25(OH)D concentrations < 20 ng/ml), which is slightly lower compared to the global prevalence of vitamin D deficiency among chronic liver disease populations ranging from 64 to 92% (Zhao et al, 2016, Falak et al, 2020.…”
Section: Discussionmentioning
confidence: 64%
“…5 In a separate study conducted by Falak et al, it was observed that a significant proportion of patients, specifically 76.5%, exhibited a shortage in vitamin D levels. 8 The elevated prevalence of vitamin D deficiency seen in these studies could potentially be attributed to a higher proportion of female participants in comparison to male patients. The general population and those with chronic liver disease both demonstrate a notable correlation between gender and the occurrence of vitamin D insufficiency.…”
Section: Discussionmentioning
confidence: 83%
“…However, other research has failed to discover any significant variation in vitamin D levels between cirrhotic and noncirrhotic patients, or between different Child-Pugh groups. 8 Vitamin D insufficiency in alcoholics and those with cholestatic liver disease has received much of the attention. So, we set out to see how common vitamin D insufficiency is and how it relates to the degree of liver dysfunction among people who have chronic liver disease of diverse etiologies.…”
Section: Introductionmentioning
confidence: 99%